Fostering Organizational Commitment in Indonesian Strartups: The Mediating Role of Work Productivity - Kharisma Kharisma; Supriandi Supriandi (CV. Era Digital Nusantara, 2026)
The rapid expansion of Indonesian startups has intensified the need for organizations to sustain employee productivity and organizational commitment in increasingly dynamic and competitive business environments. Despite this growth, empirical evidence explaining how internal organizational factors influence employee outcomes within Indonesian startups remains limited. Therefore, this study investigates the effects of leadership style, career development, and work environment on work productivity and organizational commitment among employees in Indonesian startups. A quantitative approach was employed using survey data collected from 211 respondents through a structured Likert-scale questionnaire. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3). The findings indicate that all proposed relationships are positive and statistically significant. Career development demonstrated the strongest direct organizational factor influencing organizational commitment (β = 0.357), while work productivity exerted the largest direct effect on organizational commitment (β = 0.385). Furthermore, work productivity significantly mediated the relationships between leadership style, career development, work environment, and organizational commitment. The structural model explained 55.5% of the variance in work productivity and 60.3% of the variance in organizational commitment. The study extends organizational behavior literature by demonstrating the mediating role of work productivity in connecting leadership style, career development, and work environment with organizational commitment in the context of Indonesian startups, while also providing practical guidance for startup managers seeking to strengthen employee performance and long-term organizational commitment.